A system dynamics model of climate and malaria in Colombia (2018)
Approximately 30% of the population of Colombia live in endemic lowlands at risk of getting infected with malaria. Nonetheless, it has been shown that during the last 50 years, climate variability associated with the occurrence of El Niño (the warm phase of ENSO) causes malaria outbreaks , and is highly likely that climate change will exacerbate the incidence of malaria in those endemic regions, and its emergence in non-endemic highlands, where around 70% of Colombians live. For this reason, the aim of this thesis is to develop a model capable to explain the role that climate plays on the vector-host transmission dynamics of endemic malaria in Colombia. Toward this end, a mathematical system dynamics model forced by air temperature is developed to simulate the transmission of P. falciparum in an endemic region of the Pacific low-lands of Colombia (Nuquí, Chocó). Iterated filtering, a recently developed parameter estimation technique, was used to define the unknown value of some parameters of the model, with the purpose of perform numerical simulations of the P. falciparum malaria cases. The simulations were performed using the Euler integration method and daily time steps for the period from September of 1996 to December of 2003. We found that air temperature was able to explain the malaria outbreaks that occurred in the study region in 1997, 1998, 2002 and 2003, associated with the occurrence of El Niño or the warm phase of ENSO. This results confirm similar findings of previous models developed and simulated in Colombia, and are consistent with the role that climate variability has in the origin of interannual dynamics of malaria in other parts of the world.